THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL TOWARD STUDENT'S PROBLEM SOLVING ABILITY AND CRITICAL THINKING ABILITY IN JUNIOR HIGH SCHOOL - Elly Mahrani; Nurdin Bukit; Karya Sinulingga (Universitas Negeri Medan, 2017)
This study aimed to analyze the effect of learning model problem based learning on problem solving ability and critical thinking ability of the students. This research is a quasi experimental research with two group pretest posttest design. The population of this research is all students of class VIII Junior high school 2 Kotanopan. The sample selection is done by cluster random sampling that is class VIII-1 as experiment class applied problem-based learning model and class VIII-3 as control class applied conventional learning. Instrument used in this research is instrument of problem solving ability and critical thinking ability in the form of essay test which have been declared valid by expert team. From result of research concluded that problem solving ability in student applying model of learning problem based learning better than student with conventional learning and critical thinking ability in student applying problem based learning model better than critical thinking ability to student with conventional learning.